A framework to embed communication skills across the curriculum: A design-based research approach - Johnson, S.; Veitch, Sarah; Dewiyanti, S. (University of Wollongong, 2015)
This paper will report on the development of a university-wide framework to embed communication skills in learning, teaching and assessment at Murdoch University. The framework is based on a multi-layered approach that aims to support both staff and students through an integrated set of services and resources. These include communication skills rubrics, professional development workshops and online resources for staff, and diagnostic assessment and online modules for students. Although the project has been driven by pragmatic, institutional needs, it has aimed to contribute to theoretical understandings concerning ways of embedding the teaching, learning and assessment of communication skills in higher education curricula. Alongside the development of a practical, university-wide Communication Skills Framework, the project has followed a design-based research approach to generate guiding principles for embedding communication skill across the curriculum in higher education.